2010
DOI: 10.1016/j.ccr.2010.03.011
|View full text |Cite
|
Sign up to set email alerts
|

Effective Targeting of Quiescent Chronic Myelogenous Leukemia Stem Cells by Histone Deacetylase Inhibitors in Combination with Imatinib Mesylate

Abstract: Summary Imatinib mesylate (IM) induces remission in chronic myelogenous leukemia (CML) patients but does not eliminate leukemia stem cells (LSC), which remain a potential source of relapse. Here we investigated the ability of HDAC inhibitors (HDACi) to target CML stem cells. Treatment with HDACi combined with IM effectively induced apoptosis in quiescent CML progenitors resistant to elimination by IM alone, and eliminated CML stem cells capable of engrafting immunodeficient mice. In vivo administration of HDAC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
203
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 243 publications
(210 citation statements)
references
References 43 publications
5
203
1
Order By: Relevance
“…Acetylation/deacetylation balance has been recently suggested to have a role in the development and progression of T-cell acute lymphoblastic leukemia (T-ALL), a very aggressive disease, which accounts for 10-15% of pediatric and 25% of adult ALL cases. Indeed, HDAC inhibitors (HDACi) have been recently shown to display anti-tumor activity upon glucocorticoid resistant T-ALL cell lines and patientderived blasts, confirming therapeutic efficacy observed in other tumors (for example, B-cell acute lymphoblastic leukemia, chronic myeloid leukemia and a number of solid tumors) (Tsapis et al, 2007;Zhang et al, 2010).…”
Section: Introductionmentioning
confidence: 83%
“…Acetylation/deacetylation balance has been recently suggested to have a role in the development and progression of T-cell acute lymphoblastic leukemia (T-ALL), a very aggressive disease, which accounts for 10-15% of pediatric and 25% of adult ALL cases. Indeed, HDAC inhibitors (HDACi) have been recently shown to display anti-tumor activity upon glucocorticoid resistant T-ALL cell lines and patientderived blasts, confirming therapeutic efficacy observed in other tumors (for example, B-cell acute lymphoblastic leukemia, chronic myeloid leukemia and a number of solid tumors) (Tsapis et al, 2007;Zhang et al, 2010).…”
Section: Introductionmentioning
confidence: 83%
“…126 Another report has suggested that combining histone deacetylase inhibitors (for example, LAQ824) with IM may be more effective in targeting quiescent CML stem cells than IM alone by inhibiting several genes important to the regulation of HSC maintenance and survival. 26 More recently, evidence has been found to suggest that targeting autophagy, a process that allows cells to adapt to environmental stresses, might also allow CML stem and progenitor cells to be effectively targeted. 127 Other potential strategies include induction of protein phosphatase-2A activation by FTY720 128,129 and exposure of CML stem cells to the farnesyltransferase inhibitor (BMS-214662).…”
Section: Properties That Affect Responses To Bcr-abl-targeted Therapementioning
confidence: 99%
“…19,[22][23][24] These discoveries have, in turn, reactivated a search for newer agents that can be shown to kill CML stem cells. 25,26 In addition, they have highlighted the need for better models of the human disease that will allow a more accurate prediction of the clinical utility of newer agents.…”
mentioning
confidence: 99%
“…11,12 Also, Abl TKIs for chronic myelogenous leukemia (CML) with the Bcr-Abl oncogene are not able to eradicate tumor cells, but histone deacetylase (HDAC) inhibitors can eliminate CML stem cells in combination with the Abl TKI, imatinib. 13 This indicates that a subset of tumor cells can survive treatment with molecularly targeted drugs against the addicting oncogene product through various genetic and/or epigenetic mechanisms. These observations led us to surmise that a subpopulation of lung adenocarcinoma cells in suspension should survive the combination therapy with a Src TKI and ABT-263, but may not last with a combination treatment of a Src TKI, a Bcl-2 inhibitor, and an HDAC inhibitor.…”
mentioning
confidence: 99%